Literácia financeira e endividamento pessoal: um estudo com alunos de cursos da área de negócios - Lima, Marcelo Prudêncio de (2017)
After the start of the great recession in the United States held on September 2008, the world economy suffered the first threats of the global financial crisis. In this context, increasing economic, social and technological changes in the world pointed to the urgency of the implementation of governmental actions aiming to financially educate the population. A series of international projects have been created due to these financial crises with the main objective to raise awareness worldwide of the importance of financial education. The concern about the levels of financial literacy of the population is related to the fact that not all individuals have a broad knowledge of financial issues which may affect their personal assets, and the consequences of this not understanding remit to high levels of personal debt. This study aims to analyze the relationship between the level of financial literacy and individual financial debt of undergraduate students in Business courses at University in Sao Paulo and the factors, which affect this relationship. For this purpose, the quantitative methodology was used, questionnaire with 56 questions, nominal and ordinal scales assumed as metric. The research was composed of a sample 709 students from an undergraduate Education Institution in the city of São Paulo. In the data treatment, descriptive and multivariate statistics structural equations were used, with the support of software SPSS, version 19, and R Lavaan Method. The main results showed a proposal for the modeling of the Financial Literacy variable that there was no relation between the subject's indebtedness and his / her average level of financial knowledge. This study is relevant both on the Contemporaneity of the theme as well as the gap of the scientific studies on this subject in Brazil.